(untitled) (Global Journal of Human-Social Science, 2013)
Traditionally at common law a termination of parental rights to a child resulted in the corresponding and simultaneous termination of parental responsibilities for that child. However, a jurisdictional survey of the responsibilities remaining after the termination of parental rights revealed that while not a majority, some jurisdictions sever this dyadic coupling: Parental financial responsibility remained after the termination of parental rights. While perhaps serving the immediate financial needs of the child, this study suggests that severing the two results in unacceptable consequences for the child, as well as for the parent.